Cloud security using self-acting spontaneous honeypots - Fatima Khan, Nooreen; Mohan, M (International Journal of Engineering and Technology, 2018)
Cloud Computing is growing in terms users, infrastructure, services, also security issues like: Cyber attacks are increasing day by day security community need some better mechanism to learn about attacks and which can provide an improved response against these security issues in cloud effectively. Current defences, security solutions, security equipments doesn’t cover two or all three security concepts which are prevention, detection and response. Honeypot security resource can be used to add value to the cloud security community it can cover all three security concepts if implemented intelligently.In this project a high-interaction based self-acting spontaneous honey pot, abbreviated as SAS HP, which can dynamically change its behavior after learning from an attacker, is proposed and its architecture is given which can be deployed in the cloud environment for the analysis of attack patterns and to secure cloud systems. Also, the concept that how the instances of this honey pot can be made available as a service to the customer and how this SAS HP can be deployed with in cloud is given in this report. The aim is to develop the working prototype of the proposed system in cloud environment.